1999
DOI: 10.3354/meps191053
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal fluctuations in environmental factors and variations in symbiotic algae and chlorophyll pigments in four Indo-Pacific coral species

Abstract: Marked seasonality is observed in sea-surface temperature (SST) and photosynthetically active radiation (PAR) received by shallow water corals at Phuket, Thailand (7" N latitude). This seasonality is reflected in both algal densities and algal chlorophylls (a and C?) in 4 massive species of scleractinian corals, namely Coeloseris rnayeri, Goniastrea retiformis, Porites lutea, and G. aspera. Algal numbers and algal chlorophylls are generally maximal at the end of the wet season (November) and minimal at the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
106
0
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(115 citation statements)
references
References 33 publications
(53 reference statements)
2
106
0
4
Order By: Relevance
“…Some studies have not endorsed losses in chlorophyll a and c and have even suggested an increase of these pigments in stressed and bleached corals (Szmant and Gassman 1990;Le Tissier and Brown 1996). This has been ascribed to increased nutrient availability to the remnant algae in the host or the greater loss of apical algae leaving the subsurface algae with higher chlorophyll concentrations below (Brown et al 1999). Therefore, chlorophyll a concentrations and zooxanthellae densities may not be universally applicable as early stress indicators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have not endorsed losses in chlorophyll a and c and have even suggested an increase of these pigments in stressed and bleached corals (Szmant and Gassman 1990;Le Tissier and Brown 1996). This has been ascribed to increased nutrient availability to the remnant algae in the host or the greater loss of apical algae leaving the subsurface algae with higher chlorophyll concentrations below (Brown et al 1999). Therefore, chlorophyll a concentrations and zooxanthellae densities may not be universally applicable as early stress indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction in zooxanthellae numbers during natural bleaching event was reported in six species of corals (Brown et al 1995) and in solar bleached Goniastrea aspera (Le Tissier and Brown 1996). Increased seasurface temperature (SST) and photosynthetically active radiation (PAR) experienced by shallow water corals at Phuket in Thailand also showed decreased zooxanthallae numbers on an annual basis (Brown et al 1999). In…”
Section: Discussionmentioning
confidence: 99%
“…4). Although we cannot exclude the possibility that the corals were compromised by stress-related bleaching in trial 2, in part because coral color and Symbiodinium density can be uncoupled in the early stages of bleaching (Fitt et al, 2001), we suspect that the declines in Symbiodinium density reflected the onset of routine seasonal changes in algal populations (Brown et al, 1999;Fitt et al, 2000). Such changes can be rapid, and in the Caribbean coral Montastrea faveolata, for example, seasonal declines in Symbiodinium density can occur at 2.2 × 10 6 cells cm 2 month − 1 in a non-bleaching year (i.e., when corals do not appear pale), which corresponds to a 44% reduction month − 1 from the winter maximum ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the two trials suggest that the response of back reef corals to oscillatory thermal environment may differ between periods when their tissues are well populated with, versus depleted of, Symbiodinium. When Symbiodinium densities are high, for example in the winter and spring (Brown et al, 1999;Fitt et al, 2000), corals are able to respond by reducing their Symbiodinium population in response to diurnal variations in temperature. This responsiveness may degrade, however, as Symbiodinium populations decline through seasonal effects concurrent with the end of summer and start of autumn (Brown et al, 1999;Fitt et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of chlorophyll a (and hence colour brightness) increase in response to exposure to elevated nutrients (Hoegh-Guldberg and Smith 1989; Table 2) and reduced irradiance (Falkowski and Dubinsky 1981;Dubinsky et al 1984) whereas symbiont density may decrease in response to sedimentation (Nugues and Roberts 2003) and exposure to pollutants, such as cyanide (Cervino et al 2003). However, symbiont density also varies with season (Stimson 1997;Brown et al 1999;Fagoonee et al 1999) and seawater temperature, indicating a moderate specificity to changes in water quality. Correlating colony brightness to changes in water quality also requires large spatial and temporal replication in monitoring programmes because photo-acclimatory responses occur on short timescales (Anthony and Hoegh-Guldberg 2003).…”
Section: Colony Brightnessmentioning
confidence: 99%